Análisis del engagement en las piezas publicitarias divulgadas en Facebook e Instagram para el posicionamiento de la marca Jimmy Mejía, periodo enero – abril 2024 - Pinda Vivanco, Daniela Decired (2025)
Nowadays, companies have adopted digital marketing strategies aimed at meeting people needs through streamlined processes and personalized experiences. The evolution of digital platform tools has allowed brands to design advertising campaigns that resonate with their audience and generate a meaningful compromise. In this context, analyzing engagement on social media platforms like Facebook and Instagram becomes a key tool to measure the effectiveness of digital marketing strategies implemented by the Jimmy Mejía brand, focused on the promotion of cosmetic surgery services. The strategies are important in the health industry, strengthening its presence, attracting audiences and educating them about the health services it offers. The general objective is to analyze the advertising pieces shared on Facebook and Instagram for the positioning of Jimmy Mejia’s brand. The specific objectives are to define the digital marketing strategies implemented in healthcare services; compile the content of the advertising pieces shared by the brand on both social media platforms; and evaluate the engagement perception of these advertising pieces by the brand’s managers. The methodology used was a mixed method, that is, quantitive and qualitative, analyzing posts made by the brand between January and April 2024, using a daily approach to gather precise data on themes, formats and interactions: likes, comments and shares. The results showed that Jimmy Mejia’s brand achieved 3,4% of engagement on Facebook and Instagram. Posts related to before and after images of surgical interventions achieved 34,885 interactions